2023
DOI: 10.1093/humupd/dmac040
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal GnRH antagonist protocol for ovarian stimulation during ART treatment? A systematic review and network meta-analysis

Abstract: BACKGROUND Several GnRH antagonist protocols are currently used during COS in the context of ART treatments; however, questions remain regarding whether these protocols are comparable in terms of efficacy and safety. OBJECTIVE AND RATIONALE A systematic review followed by a pairwise and network meta-analyses were performed. The systematic review and pairwise meta-analysis of direct comparative data according to the PRISMA gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…Pretreatment with estrogen, progestin, or OC can eliminate the corpus luteum, suppress endogenous FSH, restore serum FSH to normal levels, and restore the sensitivity of FSH receptors [ 14 ]. Miyoshi et al suggested that estrogen can upregulate FSH and LH receptors on granulosa cells to increase their sensitivity to Gn and synergize with FSH to promote follicular growth and proliferation of granulosa cells [ 15 ]. Meta-analysis showed that OC combined with GnRH antagonist treatment decreased the rates of ongoing pregnancy, however there was also no evidence of a difference in live birth or clinical pregnancy rates between women who were pretreated with and without estrogen [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with estrogen, progestin, or OC can eliminate the corpus luteum, suppress endogenous FSH, restore serum FSH to normal levels, and restore the sensitivity of FSH receptors [ 14 ]. Miyoshi et al suggested that estrogen can upregulate FSH and LH receptors on granulosa cells to increase their sensitivity to Gn and synergize with FSH to promote follicular growth and proliferation of granulosa cells [ 15 ]. Meta-analysis showed that OC combined with GnRH antagonist treatment decreased the rates of ongoing pregnancy, however there was also no evidence of a difference in live birth or clinical pregnancy rates between women who were pretreated with and without estrogen [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latest review by Venetis et al. included more studies and reported that fixed GnRH-ant protocol resulted in a higher ongoing pregnancy rate ( 3 , 10 ). However, reproductive characteristics vary greatly among different populations, while very few studies exist analyzing the optimal timing of GnRH-ant initiation for specific subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Inany et al reported no significant difference between the two protocols, but also emphasized the trend of higher pregnancy rate of fixed GnRH-ant protocol. The latest review by Venetis et al included more studies and reported that fixed GnRH-ant protocol resulted in a higher ongoing pregnancy rate (3,10). However, reproductive characteristics vary greatly among different populations, while very few studies exist analyzing the optimal timing of GnRH-ant initiation for specific subpopulations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations